The linguistic individual : self-expression in language and linguistics - Johnstone, Barbara (Oxford studies in sociolinguistics., 1996)
Linguists usually discuss language or dialects in terms of groups of speakers. Believing that patterns can be seen more clearly in the group than the individual, researchers often present group scores with no indication of the variation within the group. Even though linguists acknowledge thatno two individuals speak alike, few study individual variation and voice. Barbara Johnstone makes a case for the individual's importance and idiosyncrasies in language and linguistics. Using theoretical arguments and discourse analysis, along with linguistic examples from a variety of speakers and settings.